Between Autonomy and Control: Federal–Provincial Power Dynamics in Nepal’s Federal System - Gupta, Khusboo (NPRC Journal of Multidisciplinary Research, 2025)
Nepal’s adoption of a federal system, formalized by the 2015 Constitution, marked a profound shift from its historical centralized unitary structure to a three-tiered governance framework. This article examines the institutional dynamics of intergovernmental relations (IGR) within this nascent federal arrangement, focusing specifically on the federal–provincial power dynamics and the inherent tension between sub-national autonomy and central control. Drawing upon a broader doctoral study, with a particular emphasis on Madhesh Province, it explores how the coordination of policy, sharing of resources, and harmonization of administrative functions are shaped by this ongoing negotiation. The analysis highlights how the balance (or imbalance) between autonomy and control profoundly impacts the stability, efficiency, and democratic accountability of Nepal’s federal experiment. By illustrating these dynamics through the lens of Madhesh Province, a historically marginalized and strategically important region, this study offers empirically informed insights into the practicalities of decentralization and inter-tier power-sharing in a diverse socio-political landscape, contributing to the broader discourse on federalism in transitioning democracies.